2022
DOI: 10.3390/microorganisms10030590
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lithium on the Budding Yeast Saccharomyces cerevisiae upon Stress Adaptation

Abstract: Lithium salts are used in the treatment of mood disorders, cancer, and Alzheimer’s disease. It has been shown to prolong life span in several phyla; however, not yet in budding yeast. In our study, we investigate the influence of lithium on yeast cells’ viability by characterizing protein aggregate formation, cell volume, and molecular crowding in the context of stress adaptation. While our data suggest a concentration-dependent growth inhibition caused by LiCl, we show an extended long-term survival rate as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Nonetheless, a two-hour pre-adaptation to LiCl or NaCl resulted in fewer cells with aggregates upon glucose starvation. It was also shown that glucose limitation mitigates the negative effects of LiCl on cell survival, suggesting that adaptation to low glucose conditions is related to other stress pre-adaptations [16]. This is consistent with the fact that CR induces mild stress in the cell, as the levels of ROS are increased through the inactivation of catalase activity [35].…”
Section: The Effect Of Calorie Restriction On Protein Aggregation In ...supporting
confidence: 71%
See 3 more Smart Citations
“…Nonetheless, a two-hour pre-adaptation to LiCl or NaCl resulted in fewer cells with aggregates upon glucose starvation. It was also shown that glucose limitation mitigates the negative effects of LiCl on cell survival, suggesting that adaptation to low glucose conditions is related to other stress pre-adaptations [16]. This is consistent with the fact that CR induces mild stress in the cell, as the levels of ROS are increased through the inactivation of catalase activity [35].…”
Section: The Effect Of Calorie Restriction On Protein Aggregation In ...supporting
confidence: 71%
“…Since then, yeast has become an invaluable model system to study pathological conditions and ageing, including through the expression of human proteins involved in neurodegenerative disorders, such as Alzheimer's, Parkinson's and Huntington's diseases [2][3][4]. The budding yeast Saccharomyces cerevisiae has been widely used in studies of how different nutritional environments affect proteostasis and the relationship between glucose metabolism and the accumulation of misfolded proteins [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In this review, we summarise the current knowledge on the connection between protein aggregation and the depletion of glucose and how it is controlled through glucose signalling pathways.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the right, jitter plot of the intensity measured in each fluorescent focus identified. Outlier detection and removal was performed using standard interquartile methods (83, 84). C) Fluorescence micrographs of dual label strain for simultaneous observation of aggregates and key cellular compartments.…”
Section: Resultsmentioning
confidence: 99%